Odpowiedzi

2010-04-11T11:11:11+02:00
A) 0,5(2-4x)=3-x
1-2x=3-x_____/+x
1-x=3________/-1
-x=2_________/:(-1)
x=-2
b) 12y-(y+5)=10y-1
12y-y-5=10y-1
11y-5=10y-1______/-10y
y-5=-1__________/+5
y=4
c) 2(u-5)+15=3(u-4)+10
2u-10+15=3u-12+10________/-3u
-u+5=-2_________/-5
-u=-7_________/:(-1)
u=7
1 1 1
  • Użytkownik Zadane
2010-04-11T11:11:58+02:00
A) 0,5(2-4x)=3-x wynik: x= -2
0,5(2-4x)=3-x
1-2x=3-x
-2x+x=3-1
-x=2/(-1)
x=-2
b) 12y-(y+5)=10y-1 wynik : y= 4
12y-(y+5)=10y-1
12y-y-5=10y-1
12y-y-10y=-1+5
y=4
c) 2(u-5)+15=3(u-4)+10 wynik: u= 7
2u-10+15=3u-12+10
2u-3u=-12+10+10-15
-u=-7/*(-1)
u=7